Does transcutaneous nerve stimulation have effect on sympathetic skin response? - Okuyucu, E. Esra; Turhanoglu, Ayse Dicle; Guntel, Murat; Yilmazer, Serkan; Savas, Nazan; Mansuroglu, Ayhan (Elsevier Sci Ltd, 2018)
Objective: This study examined the effects of transcutaneous electrical nerve stimulation (TENS) on the sympathetic nerve system by sympathetic skin response test. Methods: Fifty-five healthy volunteers received either: (i) 30 minutes TENS (25 participants) (ii) 30 minutes sham TENS (30 participants) and SSR test was performed pre- and post-TENS. The mean values of latency and peak-to-peak amplitude of five consecutive SSRs were calculated. Results: A significant amplitude difference was found between TENS and sham TENS group both in right and left hand (p = 0.04, p = 0.01, respectively). However there was no significant latancy difference between two groups (p>0.05). Conclusion: TENS has an inhibitory effect on elicited SNS responses when compared with sham TENS control group. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Sympathetic skin response; Transcutaneous nerve stimulation; Electrophysiolgy